Bibliometric and visual analysis in the field of macrophages in Traditional Chinese Medicine from 2003 to 2023 - Zhang, Wenxin; Zhao, Kaidi; Ma, Ruimin; Ma, Minghan; Du, Yuqiong; Fang, Peng (Frontiers in Immunology, 2025)
ObjectiveMacrophages are increasingly recognized as crucial therapeutic targets in the treatment of diverse pathological conditions. While considerable research has focused on macrophage-related mechanisms within Traditional Chinese Medicine (TCM), there remains a notable absence of comprehensive quantitative analyses in this field. This study aims to examine the evolutionary trajectory of macrophage-related research in TCM from 2003 to 2023, providing insights to guide future investigative directions.MethodsWe searched for articles published between 2003 and 2023 from the Web of Science Core Collection (WoSCC) database and analyzed them using R software, VOSviewer and CiteSpace.ResultsA total of 1,823 documents were obtained through the search. The results indicated that the number of publications between 2003 and 2023 exhibited an upward trend, with the majority of these documents originating from Chinese academic institutions and authored by Chinese scholars. This observation suggests a potential correlation with the growing prominence of Chinese medicine within China. Macrophage polarizations, a prominent focus in the study of macrophages, has also assumed an increasingly significant role in the domain of macrophages in TCM-related disciplines. The publication of these results also suggests that targeting macrophages in TCM for the treatment of some diseases is very promising, especially in ulcerative colitis, tumor-related diseases, and some liver diseases. This study provides a more comprehensive analysis of the current status and significant areas of research in the field of macrophage research in TCM, offering valuable insights for prospective research endeavors.ConclusionMacrophage-related studies in TCM have garnered increasing attention from global scholars from researchers worldwide, and are expected to become a hotspot for targeting macrophages to develop new drugs to treat diseases in the future. This study comprehensively analyzes the current status and hotspots of macrophages in Chinese medicine, which can provide valuable references for future research.